Port marketing as a tool of competitive advantage - Poh, Kevin Tze Wei. (2010)
The importance of marketing in port management is gradually being recognized by researchers and port operators all over the world as a tool to remain competitive in an increasingly challenging environment. This research project explores the extent of marketing conducted in the Port of Singapore and examines whether current marketing strategies and activities lead to competitive advantage. The literature review in Chapter 2 establishes understanding of marketing constructs and discusses findings of previous studies. Chapter 3 discusses the development of the research methodology. Chapter 4 reports the marketing strategies and activities undertaken by Jurong Port and PSA Singapore within 3 dimensions – customer analysis, marketing mix and customer relationship management. Also, it examines port choice reasons from freight forwarders’ and shipping lines’ perspectives and argues that a marketing capability helps to sustain a competitive advantage for the Port of Singapore. Chapter 5 presents the conclusion.